1996
DOI: 10.1164/ajrccm.153.1.8542125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mouth opening on upper airway collapsibility in normal sleeping subjects.

Abstract: We investigated the influence of mouth opening on upper airway (UA) collapsibility in six healthy sleeping volunteers. UA collapsibility was measured during continuous negative airway pressure trials that consisted of the progressive decrease in pressure in a nasal mask, with simultaneous recording of esophageal pressure and instantaneous flow. Measurements were made under two experimental conditions: mouth closed (MC), and mouth open (MO). Cephalometric measurements were obtained with subjects awake in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
2
13

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(141 citation statements)
references
References 27 publications
4
122
2
13
Order By: Relevance
“…8 Furthermore, mouth opening is an inherent feature of oronasal mask use, and mouth opening has previously been demonstrated to increase upper airway collapsibility. 23 Another possible explanation is that breathing through the mouth with an oronasal mask leads to the soft palate being pushed posteriorly, which may counteract the opening forces of nasal airflow and lead to a narrower airway than seen when using a nasal mask. In support of this hypothesis is a recent study using magnetic resonance imaging, which showed that nasal masks were more effective at opening the upper airway in the retropalatal region (but not retroglossal) compared to oronasal masks.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, mouth opening is an inherent feature of oronasal mask use, and mouth opening has previously been demonstrated to increase upper airway collapsibility. 23 Another possible explanation is that breathing through the mouth with an oronasal mask leads to the soft palate being pushed posteriorly, which may counteract the opening forces of nasal airflow and lead to a narrower airway than seen when using a nasal mask. In support of this hypothesis is a recent study using magnetic resonance imaging, which showed that nasal masks were more effective at opening the upper airway in the retropalatal region (but not retroglossal) compared to oronasal masks.…”
Section: Discussionmentioning
confidence: 99%
“…Mouth opening has been shown to increase upper airway collapsibility. 35 In contrast to previous reports, in our study NEP was applied through a nasal mask in the supine position. Our method therefore may convey more relevant information for patients under investigation for OSA.…”
Section: Discussionmentioning
confidence: 82%
“…1 It has been reported that upper airway collapsibility and resistance during sleep were significantly higher in subjects who were breathing through the mouth than in those who were breathing through the nose, which is different from that seen during the conscious state. 2,3 Other reasons for nasal breathing over mouth breathing during normal sleep are based on the physiological effects of decreased nasal airflow. First, bypassing the nasal airway can lead to reduced nasal receptor activation, deactivation of the nasal ventilatory reflex, and reduced spontaneous ventilation.…”
Section: Of Patterns the Nasal Airway And Sdbmentioning
confidence: 99%
“…Mouth opening increased upper airway collapsibility during sleep, which is different from that seen when awake. 2 Fitzpatrick et al 3 confi rmed that during sleep, upper airway resistance during oral breathing was 2.5 times higher than that during nasal breathing. Mouth opening may be associated with narrowing of the pharyngeal lumen and decreases in the retroglossal diameter.…”
mentioning
confidence: 99%